Sowing the Seeds of Recovery: A Qualitative Study of Women in Recovery From Addiction and Victimization - Edwards, Katie M. (Violence against women, 2025)
The purpose of this study was to understand the lived experiences of women with histories of victimization and addiction who were recently admitted to a sober living home (SLH). From the 17 interviews conducted, five themes (i.e., experiences of violence, challenges leaving an abusive relationship, chaos, using substances to cope, and social support) and one constitutive pattern (i.e., sowing the seeds of recovery) emerged from the data. These results highlight the importance of social support in promoting recovery and that social support may foster positive relationships with safe and trustworthy individuals as well as empower and support others with similar experiences.